Challenging school experiences of unavoidable absence and return for young people with chronic health conditions in English secondary schools: a qualitative, multi-informant study - Lauren Herlitz; Matthew A. Jay; Claire Powell; Jessica Deighton; Ruth Gilbert; Ruth Blackburn (Frontiers in Education)
IntroductionSchool absences rates in England have remained high since the COVID-19 pandemic and reducing absence is a policy priority. Evidence shows that young people with chronic health conditions have higher school absence and worse educational outcomes. We examined the perspectives of young people, caregivers and school staff on school absence and return for English secondary school pupils with chronic health conditions.MethodsWe recruited participants through professional networks and health/education organizations, emailing a link to an online qualitative survey. Data analysis was thematic.ResultsWe received survey responses from 12 young people, 33 caregivers, and 18 school staff. Across the young people and caregiver sample (n = 45), two-thirds reported that they or their child had 2 + conditions; 49 different conditions were reported. The nature of absence and its predictability varied. While absent, participants reported that young people fell behind with schoolwork and were isolated from their peers; school support was described as patchy or non-existent. On return to school, young people’s health affected their performance in class and exams and inclusion with peers. Attending school, and its associated stresses, could also negatively impact on young people’s conditions. Young people and caregivers reported that pupils needed caring, reassuring behavior from staff and support to catch-up and succeed academically. Gaps were identified in staff knowledge.DiscussionPolicy and practice should focus on mitigating the impact of unavoidable health-related absence.